(untitled) (Innovative professional education, 2024)
The psychological assistance service is designed to improve the quality of operational and service tasks, as well as the effective functioning of the entire system of National Police bodies; minimize the damage caused by exposure to life-threatening and psychogenic factors on workers; promote the preservation of human potential, maintain a high level of professional and combat readiness of employees. Thus, the service of psychological support for the operational activities of the bodies and units of the National Police of Ukraine can rightfully be considered as a specific type of social service, which is the main subject of the implementation of social work in law enforcement agencies.